Effect of Workload, Emotional Intelligence and Organizational Support for the Work Spirit of the Samatiga Police - Suriadi, Mimin; Habibi, Rahmat (Economic: Journal Economic and Business, 2023)
The author chose the location and research object at the Samatiga Police, West Aceh. Based on initial observations, the author concludes his hypothesis, namely that it is suspected that workload, emotional intelligence and organizational support have an influence on police morale at the Samatiga Police. After carrying out further research, starting from the data collection process to conducting statistical data processing, the results of this research can be concluded as follows. From the results of the ANOVA F test (simultaneous test), the variables X1, X2 and X3 obtained a sig value of 0.001<0.05. So in this case it means that variables X1, X2 and X3 simultaneously (together) have a positive and significant influence on variable Y. So the conclusion is that the hypothesis has been answered, namely Workload, Emotional Intelligence and Organizational Support have a positive and significant influence on Police Job Satisfaction at the Samatiga Police.